Optical property analysis of chitosan-graphene quantum dots thin film and dopamine using surface plasmon resonance spectroscopy - Kamal Eddin, Faten Bashar; Yap, Wing Fen; Sadrolhosseini, Amir Reza; Liew, Josephine Ying Chyi; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim (Springer New York, 2022)
In this study, surface plasmon resonance (SPR) technique has been utilized to characterize the optical properties of chitosan-graphene quantum dots (CS-GQDs) thin film and dopamine (DA). Theoretical fitting of SPR dips yielded refractive indices of DA solutions and CS-GQDs thin films, as well as the thickness of the thin film. For DA solution, n and k values were the same as deionized water for all concentrations. The values of n and k for CS-GQDs thin film were 1.6990 and 0.1302 respectively before contacting DA. The experimental SPR reflectance curves obtained using CS-GQDs thin film were shifted continuously to the right with increasing DA concentrations. After adsorption of DA molecules, both n and thickness of the CS-GQDs thin film increased, while the value of k decreased. This, in turns, enhanced the SPR sensitivity towards DA. The obtained results underscore the appropriate and sufficient potential of the used technique to measure refractive index variations in real-time when very low concentration was used (1 fM) with refractive index sensitivity of 10.186°/RIU.